2020
DOI: 10.1136/bmjopen-2020-038386
|View full text |Cite
|
Sign up to set email alerts
|

Recipient and instructor perspectives of an adapted exercise-based fall prevention programme for adults aged 50+ years with vision impairment: a qualitative study nested within a randomised controlled trial

Abstract: ObjectiveOlder adults with vision impairment currently have no access to tailored fall prevention programmes. Therefore, the purpose of this study, nested within an ongoing randomised controlled trial (RCT), is to document the adaptation of an existing fall prevention programme and investigate the perspectives of instructors involved in delivery and the older adults with vision impairment receiving the programme (recipients).DesignWe documented programme adaptations and training requirements, and conducted sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…Intriguingly, our study revealed that some older adults (≥ 74 years old) perceived themselves as “too old” to engage in fall prevention programs, while prior research suggests that younger older adults (≤ 65 years old) may view themselves as “too healthy” to participate despite previous falls. 37 These divergent attitudes toward program participation emphasize the need for tailored strategies to address motivational barriers in different age groups.…”
Section: Discussionmentioning
confidence: 99%
“…Intriguingly, our study revealed that some older adults (≥ 74 years old) perceived themselves as “too old” to engage in fall prevention programs, while prior research suggests that younger older adults (≤ 65 years old) may view themselves as “too healthy” to participate despite previous falls. 37 These divergent attitudes toward program participation emphasize the need for tailored strategies to address motivational barriers in different age groups.…”
Section: Discussionmentioning
confidence: 99%